2019
DOI: 10.1111/eva.12881
|View full text |Cite
|
Sign up to set email alerts
|

Population genomics supports clonal reproduction and multiple independent gains and losses of parasitic abilities in the most devastating nematode pest

Abstract: The root-knot nematodes are the most devastating worms to worldwide agriculture with Meloidogyne incognita being the most widely distributed and damaging species. This parasitic and ecological success seems surprising given its supposed obligatory clonal reproduction. Clonal reproduction has been suspected based on cytological observations but, so far, never confirmed by population genomics data. As a species, M. incognita is highly polyphagous with thousands of host plants. However, different M. incognita iso… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
59
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(62 citation statements)
references
References 64 publications
3
59
0
Order By: Relevance
“…The 11 other isolates come from different locations across Brazil, and present four different ranges of compatible hosts (referred to as R1, R2, R3, R4, see sup. Fig S4) and currently infected crop species (Koutsovoulos et al 2020). Pool-seq paired-end Illumina data has been generated for all these isolates.…”
Section: Fig 2: Per-copy Identity Rate With Consensusmentioning
confidence: 99%
See 3 more Smart Citations
“…The 11 other isolates come from different locations across Brazil, and present four different ranges of compatible hosts (referred to as R1, R2, R3, R4, see sup. Fig S4) and currently infected crop species (Koutsovoulos et al 2020). Pool-seq paired-end Illumina data has been generated for all these isolates.…”
Section: Fig 2: Per-copy Identity Rate With Consensusmentioning
confidence: 99%
“…The mechanisms underlying the adaptability of parthenogenetic RKN without sex remain elusive. Recent population genomics analyses showed that only a few single nucleotide variations (SNV) could be identified by comparing different Brazilian M. incognita isolates showing distinct ranges of host compatibility (Koutsovoulos et al 2020). Addition of further isolates from different geographical locations across the world did not substantially expand the number of variable positions in the genome.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Koutsovoulos et al 65 sequenced the genomes of 11M. incognita isolates race 1 to 4 infecting different host plant across Brazil (including the race 3, used in this study) and showed that cumulative fixed divergence across these Brazilian isolates and the reference genome (M. incognita strain Morelos) reached approximately 0.02% of the nucleotides.…”
Section: Discussionmentioning
confidence: 75%